The mystery of photometric twins DES17X1boj and DES16E2bjy. Issue 4 (13th April 2020) - Pursiainen, M; Gutiérrez, C P; Wiseman, P; Childress, M; Smith, M; Frohmaier, C; Angus, C; Castro Segura, N; Kelsey, L; Sullivan, M; Galbany, L; Nugent, P; et al.
ABSTRACT: We present an analysis of DES17X1boj and DES16E2bjy, two peculiar transients discovered by the Dark Energy Survey (DES). They exhibit nearly identical double-peaked light curves that reach very different maximum luminosities ( M r = −15.4 and −17.9, respectively). The light-curve evolution of these events is highly atypical and has not been reported before. The transients are found in different host environments: DES17X1boj was found near the nucleus of a spiral galaxy, while DES16E2bjy is located in the outskirts of a passive red galaxy. Early photometric data are well fitted with a blackbody and the resulting moderate photospheric expansion velocities (1800 km s −1 for DES17X1boj and 4800 km s −1 for DES16E2bjy) suggest an explosive or eruptive origin. Additionally, a feature identified as high-velocity Ca ii absorption (v ≈ 9400 km s −1 ) in the near-peak spectrum of DES17X1boj may imply that it is a supernova. While similar light-curve evolution suggests a similar physical origin for these two transients, we are not able to identify or characterize the progenitors.